The SIGLEC14 null allele is associated with Mycobacterium tuberculosis- and BCG-induced clinical and immunologic outcomes - Graustein, A; Horne, D; Fong, J; Schwarz, F; Mefford, H; Peterson, G; Wells, R; Musvosvi, M; Shey, M; Hanekom, W; Hatherill, M; Scriba, T; et al. (Elsevier, 2017)
Humans exposed to Mycobacterium tuberculosis (Mtb) have variable susceptibility to tuberculosis (TB) and its outcomes. Siglec-5 and Siglec-14 are members of the sialic-acid binding lectin family that regulate immune responses to pathogens through inhibitory (Siglec-5) and activating (Siglec-14) domains. The SIGLEC14 coding sequence is deleted in a high proportion of individuals, placing a SIGLEC5-like gene under the expression of the SIGLEC14 promoter (the SIGLEC14 null allele) and causing expression of a Siglec-5 like protein in monocytes and macrophages. We hypothesized that the SIGLEC14 null allele was associated with Mtb replication in monocytes, T-cell responses to the BCG vaccine, and clinical susceptibility to TB. The SIGLEC14 null allele was associated with protection from TB meningitis in Vietnamese adults but not with pediatric TB in South Africa. The null allele was associated with increased IL-2 and IL-17 production following ex-vivo BCG stimulation of blood from 10 week-old South African infants vaccinated with BCG at birth. Mtb replication was increased in THP-1 cells overexpressing either Siglec-5 or Siglec-14 relative to controls. To our knowledge, this is the first study to demonstrate an association between SIGLEC expression and clinical TB, Mtb replication, or BCG-specific T-cell cytokines.